Studi Literatur: Efektivitas Daun Mimba sebagai Pestisida Nabati Pengusir Ulat Grayak pada Tanaman Jagung: pestisida nabati; mimba; ulat grayak; tanaman jagung - Achmad Choirul Fatikhin; Rosdiana , Laily; Dian Roqobih, Fikky (innofarm, 2023)
This study aimed to investigate the use of botanical pesticides from Neem (Azadirachta indica A. Juss.) as an alternative control measure for fall armyworm (Spodoptera frugiperda) on maize plants. Botanical pesticides had the potential to replace chemical pesticides in efforts to reduce negative impacts on the environment and human health. This study used a literature review method with secondary data obtained from Science and Technology Index (SINTA), Google Scholar, Research Gate, IOP Science, and Science Direct databases, covering the period of 2015-2023, using keywords such as botanical pesticides, Neem, and fall armyworm. The results of the study indicated that the use of Neem extract (Azadirachta indica) as a botanical insecticide was effective and environmentally friendly in controlling fall armyworm infestation on maize plants. Neem oil spray was shown to reduce fall armyworm infestation in maize plants in several studies. Natural chemical compounds in Neem such as Azadirachtin, salannin, meliantriol, and Nimbin had insecticidal effects, inhibiting pest insect growth, reducing feeding behavior, reducing egg production and hatching, and increasing mortality. The use of botanical pesticides from Neem (Azadirachta indica A. Juss.) had the potential as an effective and environmentally friendly alternative for fall armyworm control on maize plants. However, further research was needed to optimize the use of botanical pesticides from Neem in controlling fall armyworm and evaluating their impacts on the environment and human health.